Infant development in family context: call for a genetically informed approach - Parade, Stephanie H.; McGeary, John; Seifer, Ronald; Knopik, Valerie (Frontiers in Genetics, 2012)
We call for a genetically informed approach in the examination of infant social and emotional development in family context. We recommend that scholars conceptualize family functioning as occurring on three unique levels: the parent-child dyad, the inter-parental dyad, and whole family functioning. Although advances in the area of understanding genetic variation in infants as a potential moderator of the influence of parent-child dyadic functioning have been made over the past decade, it is time to widen this inquiry to consider genetic variation in infants as a potential moderator of the influence of inter-parental dyadic and whole family functioning as well. A critical review of the literature also calls for additional examination of genetic variation in infants as a moderator of positive contextual influences, the integration of unique temperament variables with studies of infant genotype, consideration of the role of the gene-environment correlation, and epigenetic effects. Furthermore, we call for the application of genetically-informed research methods to these questions. Expanding knowledge in this area has the potential to refine treatment and prevention efforts aimed at promoting infant social and emotional development.